Does debt predict growth? An empirical analysis of the relationship between total debt and economic output - Willem Vanlaer; Wim Marneffe; Lode Vereeck; Johan Vanovertveldt (European Journal of Government and Economics (EJGE), 2015)
Although the recent global financial crisis has stimulated a vast amount of research on the impact of public debt on economic growth and also increasingly on the role of private credit, the total levels of indebtedness of an economy have largely been ignored. This paper studies the impact of the total level of and increases in debt-to-GDP on economic growth for 26 developed countries in the short, medium and longer term. We analyse whether we can predict the future level of growth, simply by looking at the total level of debt, or increases in that debt level. We find that there is a negative correlation between high levels of debt and short term economic growth, but that this effect tapers in the medium and long term. Similarly, we find that rapid debt accumulation is negatively related to economic growth over the short term, the impact is less pronounced over the medium term and is non-existent over the long term.
Keywords: 330; Public Debt; Government Debt; Private Debt; Growth; OECD Countries